Achieving sustainable construction through the integration of lean construction and ESG: A critical review - Agustin, Nina; Koestoer, Raldi Hendro (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: With the expansion of construction sector, being environmentally responsible and sustainable has become crucial. Given its significant impact on carbon emissions and resource consumption, the industry is encouraged to adopt approaches that enhance efficiency while addressing environmental, social, and economic concerns. Methods: This study employed a systematic review and bibliometric analysis using VOSviewer software to qualitatively examine the alignment between Lean Construction and the ESG framework in the construction industry. Findings: Lean Construction (LC), closely aligned with Sustainability and the Environmental, Social, and Governance (ESG) framework, offers a strategy focused on continuous improvement, waste reduction, and value creation. The integration of LC and ESG can accelerate the achievement of sustainability through waste reduction, resource efficiency, and improved worker welfare and better project governance. The objective of this study was to explore the trends associated with the alignment between these two methods in the world of construction and opportunities for further research development. Conclusion: This study conducted through systematic review and bibliometric analysis employing VOS viewer software for qualitative analysis. For future research opportunities there will be many related topics such as design or methodology, waste reduction, sustainable building, circular economy, lean tools and carbon footprint. Novelty/Originality of this article: This article lies in its integrated exploration of Lean Construction and the ESG framework through a systematic bibliometric analysis, offering new insights into their synergistic potential for advancing sustainability in the construction industry.